2016
DOI: 10.1016/j.cej.2016.04.066
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen production via methane pyrolysis in a liquid metal bubble column reactor with a packed bed

Abstract: Methane pyrolysis experiments using a quartz glass-steel bubble column reactor filled with liquid tin and cylindrical quartz glass rings serving as a packed bed were conducted at various liquid metal temperature levels in the range of 930 °C to 1175 °C. Besides the liquid metal temperature, special attention was paid to the influence of the feed gas volume flow rate in the range of 50-200 mln/min and the inlet feed gas dilution with nitrogen. Increasing liquid metal temperatures resulted in increasing hydrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
92
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(106 citation statements)
references
References 23 publications
6
92
0
8
Order By: Relevance
“…Using a liquid metal bubble column reactor solves the problem of carbon deposition as carbon is insoluble in molten metal and can be easily scraped off from top of the molten metal surface.57% CH 4 conversion rate was achieved by bubbling natural gas through mott porous metal filters,in a bed of either tin or tin and silicon carbide at 750°C by [42].Liquid metal coolants from fourth generation nuclear reactors were considered as the heat source.Molten tin was used as the heat transfer metal by [43].They found that molten tin does not have any catalytic impact but inhibits production of intermediate products. Molten tin was used in a quartz glass-steel bubble column reactor by [44],to conduct experimental studies on decomposition of methane.Maximum hydrogen yield of 78% was achieved during the experiments.Only 1.5% intermediate products were formed during all experimental runs.Liquid metal temperature,gas flow rate and residence time were found to be the most important factors affecting hydrogen production.Carbon formed during the reaction was found to be completely separated on the top surface of the liquid metal.Trace amounts of carbon nano-tubes(CNT) were formed at the quartz glass reactor wall.Small quantity of carbon particles were transported with the off-gas stream.Effect of inlet gas dilution was evaluated in the study,by mixing the inlet stream with nitrogen.In their earlier work,the researchers had achieved a conversion efficiency of 30% [45].A process set-up,for industrial production of hydrogen was proposed by [40],using molten iron in the bubble column reactor and using an electric heater to produce molten metal.By conducting a techno-economic analysis,the authors estimated that hydrogen can be produced at 1.72 kg − 1,with a natural gas price of $3 MMBTU − 1.A new system for production of H 2 using methane pyrolysis in a liquid metal bubble column reactor coupled with a DRI shaft furnace and EAF system has been proposed.…”
Section: Liquid Metal Reactor For Methane Pyrolysismentioning
confidence: 99%
“…Using a liquid metal bubble column reactor solves the problem of carbon deposition as carbon is insoluble in molten metal and can be easily scraped off from top of the molten metal surface.57% CH 4 conversion rate was achieved by bubbling natural gas through mott porous metal filters,in a bed of either tin or tin and silicon carbide at 750°C by [42].Liquid metal coolants from fourth generation nuclear reactors were considered as the heat source.Molten tin was used as the heat transfer metal by [43].They found that molten tin does not have any catalytic impact but inhibits production of intermediate products. Molten tin was used in a quartz glass-steel bubble column reactor by [44],to conduct experimental studies on decomposition of methane.Maximum hydrogen yield of 78% was achieved during the experiments.Only 1.5% intermediate products were formed during all experimental runs.Liquid metal temperature,gas flow rate and residence time were found to be the most important factors affecting hydrogen production.Carbon formed during the reaction was found to be completely separated on the top surface of the liquid metal.Trace amounts of carbon nano-tubes(CNT) were formed at the quartz glass reactor wall.Small quantity of carbon particles were transported with the off-gas stream.Effect of inlet gas dilution was evaluated in the study,by mixing the inlet stream with nitrogen.In their earlier work,the researchers had achieved a conversion efficiency of 30% [45].A process set-up,for industrial production of hydrogen was proposed by [40],using molten iron in the bubble column reactor and using an electric heater to produce molten metal.By conducting a techno-economic analysis,the authors estimated that hydrogen can be produced at 1.72 kg − 1,with a natural gas price of $3 MMBTU − 1.A new system for production of H 2 using methane pyrolysis in a liquid metal bubble column reactor coupled with a DRI shaft furnace and EAF system has been proposed.…”
Section: Liquid Metal Reactor For Methane Pyrolysismentioning
confidence: 99%
“…The actual removal of elements does not necessarily occur in proportion to the concentration in the alloy, so that a near‐surface zone may develop in the solid that is depleted in the elements that exhibit comparatively high solubility in the liquid metal. The most prominent example is nickel (Ni) in steels . An originating depletion zone also constitutes a loss of material not only if penetrated by the liquid metal but especially if this is the case.…”
Section: Corrosion and Corrosion Protection In Liquid‐metal Systemsmentioning
confidence: 99%
“…The most prominentexample is nickel (Ni)i ns teels. [28][29][30] An originating depletion zone also constitutes al oss of material not only if penetratedb yt he liquid metal but especially if this is the case.A lternatively,m etallic elements present in the ma- terial may combine with constituents of the liquid metal to form intermetallic phases. [28,29] Necessarily,t he liquid metal is then saturated locally at the materials urface in the involved material element(s), but in contrast to purely solution-based degradation, the formation of intermetallic phases and, therefore,c orrosion would proceed even if the liquid metal was globallys aturated.…”
Section: Corrosion and Corrosion Protection In Liquid-metal Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the main concerns about these methods is the extraction of carbon from the reactor, which forms very hard graphitic deposits at high temperatures. Additional technologies are under development, such as the utilization of a liquid metal reaction media (Geißler et al, 2015(Geißler et al, , 2016.…”
Section: Natural Gas Decarbonizationmentioning
confidence: 99%